Control method for ventilated supercavitating vehicle considering planing avoidance and stability. (August 2019) - Kim, Seonhong; Kim, Nakwan
In this study, we focus on realizing planing avoidance control for a ventilated supercavitating vehicle while considering stability issues. A ventilated supercavitating vehicle can control the size of a cavity by blowing gas into the cavity. By controlling the cavity size, planing can be prevented in advance. However, the vehicle loses its stability because of the growth of the cavity. Additional control input is determined to prevent "stability loss" based on linear stability analysis while considering ventilation system dynamics. The proposed controllers are applied to a supercavitating vehicle model, and numerical simulations are performed to analyze the physical feasibility and performance of the designed controllers. The results show that the proposed control methods can maintain vehicle stability during maneuvering operations and can eliminate planing.